2017
DOI: 10.1007/s11998-017-9920-y
|View full text |Cite
|
Sign up to set email alerts
|

Fully bio-based aliphatic thermoset polyesters via self-catalyzed self-condensation of multifunctional epoxy monomers directly extracted from natural sources

Abstract: The use of bio-based raw material is regarded as a sustainable way to address environmental concerns. A naturally occurring monomer, 9,10-epoxy-18-hydroxyoctadecanoic acid (EFA), was retrieved from outer birch bark. A series of model experiments revealing relative reaction rates for epoxide, carboxylic acid, and alcohol functional groups was investigated. Real-time Fourier transform infrared spectroscopy and nuclear magnetic resonance were used to follow the different model experiments. The results on the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Commonly, polymeric resins are categorized into epoxy and ester ones, in which ester resins are utilized for low-performance applications while epoxy resins for high performance [ 30 , 36 , 138 , 139 ]. Epoxy resins have more adhesion tendency to the surface of glass and carbon fibers than ester resins.…”
Section: Applications Of Lignin-based Resinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, polymeric resins are categorized into epoxy and ester ones, in which ester resins are utilized for low-performance applications while epoxy resins for high performance [ 30 , 36 , 138 , 139 ]. Epoxy resins have more adhesion tendency to the surface of glass and carbon fibers than ester resins.…”
Section: Applications Of Lignin-based Resinsmentioning
confidence: 99%
“…Several studies have been reported to modify the lignin and enhance compatibility with polymers and mechanical properties for high-performance applications to overcome these drawbacks. Up to now, a large amount of research has been performed on bio-based thermoplastics such as bismaleimide/eugenol [ 17 ], poly(lactic acid) [ 18 ], bio-poly(ethylene terephthalate) [ 19 ], poly(butylene succinate) [ 20 ], polyhydroxyalkanoates [ 21 , 22 ], poly(ethylene 2,5-furandicarboxylate) [ 23 ], and also on thermosets such as itaconic acid [ 24 ], isosorbide [ 25 ], composite of cardanol novolac/bismaleimide [ 26 ], plant oil [ 27 , 28 ], eugenol [ 29 ], and polyesters [ 30 ]. On the other hand, average research progress has been published on preparing thermoplastic and thermosets resins with lignin.…”
Section: Introductionmentioning
confidence: 99%
“…The full procedures of the retrieval of the different fatty acids can be found in literature. 43 EMO was retrieved by methanolysis at 60 C from epoxidized linseed oil. The obtained methyl esters were rst extracted in nheptane/deionized water (1 : 1) 4 times and then puried by column chromatography in n-heptane/EtOAc gradient solution.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the development includes a considerable amount of laboratory work, from synthesis and mixing of ingredients to the testing of the effectiveness and durability of coatings [12]. With coatings having to ensure adequate protection for as long as possible, laboratory testing often takes place under strict conditions that require well-trained professionals and expensive laboratory equipment.…”
Section: Introductionmentioning
confidence: 99%